A bone of contention: teacher evaluation system in Greece. (2019) - Papakonstantinou, Panagiotis; Kolympari, Tania
This paper explores the views of primary and secondary education teachers and their unions on the most recent Act of Parliament concerning the evaluation of teachers in Greece (Decree 152/2013). It examines the extent to which research participants agree with the proposed evaluation system taking into consideration the institutional framework; this paper also tries to achieve an understanding of the evaluation mechanisms in relation to the technocratic and transformative assessment model. Based on the analysis of qualitative data, it is found that participants are dissatisfied with the recent Parliament Act. Most teachers consider that education evaluation should be undertaken by the state and the administrative hierarchy, while fewer adopt a rather cooperative approach, based on a quasi-equal balance of power between actors in the educational process and recipients. Teachers' unions seem to maintain a visionary view, which largely relies on technocratic perception.